Developing the professional capacity of preschool teachers through pedagogical training activities - Ho, Van-Thong; Le, Thi-Kim Anh; Nguyen, Van-De; Phan, Trong-Nam; Tran, Van-Dat (Journal of Education and e-Learning Research, 2024)
The primary purpose of educational programs is to enhance students’ knowledge and skills through pedagogical training activities. However, preschool teachers in Vietnam face limitations in their professional capacity. Thus, this study aimed to address issues by evaluating the level of implementation of pedagogical training activities for preschool education students. The study used a scale for students’ pedagogical practice activities to gather quantitative data from 629 participants (managers, lecturers and preschool teachers) in Dong Thap province in Vietnam to assess the extent of implementation of pedagogical training activities for preschool education students. The results showed that preschool teachers may not possess the essential knowledge of pedagogical practices. Pedagogical training uses conventional work-and-activity techniques despite the fact that it prioritizes innovation. Moreover, all school managers, teachers and students recognized the necessity of developing the professional capacity of preschool teachers. These findings illustrate the critical need for revitalizing educational approaches that are consistent with Vietnam’s developing preschool teacher professional development context. The present study proposes some measures to innovate pedagogical practice activities in order to meet the requirements for developing the professional capacity of preschool teachers in Vietnam. Such initiatives hold promise for reshaping the educational landscape and fostering a culture of continuous improvement within the primary education sector of Vietnam.